Revealing the diagnosis of androgen insensitivity syndrome in adulthood. Issue 7517 (15th September 2005) - Conn, Jennifer; Gillam, Lynn; Conway, Gerard S
Abstract : It is always going to be difficult for a woman to find out that she is genetically male. What are the ethical issues generated by being confronted by outdated practice on disclosure?